Findings From International Surveys Providing a Snapshot of the State of KM From a Practitioner Point of View - Nicholas J Milton (Journal of Entrepreneurship, Management and Innovation)

(untitled)
Data collected through an online survey and through a number of detailed company assessments throw light on the relative strengths and weaknesses of different elements of Knowledge Management (KM) frameworks as applied globally. The online survey - a quick self-administered test, shows the strongest elements within the framework to be Technology and Behaviors and Culture. The weakest elements are KM Governance and KM Roles. The assessment - a detailed diagnostic process based on in-depth interviews, shows the strongest elements within the framework to be Technology and the Discussion of Knowledge. The weakest elements are KM Governance and KM Roles. a comparison of the results from the two sources is reassuringly close. More data may allow a more detailed analysis. Preliminary results suggest that national culture may influence the development of Knowledge Management Frameworks, with a correlation between strong Individuality and weak KM Governance and Roles. Keywords: Knowledge Management Survey, Knowledge Management Assessment, Knowledge Management Benchmark, Knowledge Management Framework, Knowledge Management Roles, Knowledge Management Technology, Knowledge Management Governance